Arsenic in drinking water and birth outcomes: a study of the Bangladesh Integrated Nutrition Programme - Jakariya, Md.; Sarkar, Md. Quaiyum; Sultana, Samina (BRAC Research and Evaluation Division (RED), 2020)
This paper assesses the impact of arsenic (As) exposure on pregnancy outcomes in Bangladesh. A total of 261 villages from 3 highly As contaminated upazilas of two districts were selected for this study. The upazilas were Faridpur sadar ofFaridpur district and Matlab and Shahrasti of Chandpur district. Data were collected from 742 women under 106 CNCs from 100 villages ofFaridpur Sadar, 710 women from 55 villages under 80 CNCs of Matlab, and 73 7 women under 33 CNCs from 106 villages of Shahrasti upazila. Water samples were collected from the tubewells (TWs) where from the pregnant mothers were drinking water, at least during the year 2002 for analysis in the laboratory with Atomic Absorption Spectrophotometric (AAS) method. A total of 2,189 women who gave births in 2002 participated in the study. Their mean age was 26.52 years, the mean duration of As exposure of the participants was 6 years, and the median was 7 years. The majority of them (72%) used As contaminated water (>50 ppb) for drinking purpose during their last pregnancies. The mean and median As concentration of the TW water of the study participants was 158.21 and 151 ppb respectively, ranging from non-detectable level to 668 ppb. Overall incidence of spontaneous abortion, stillbirth, premature birth, low birth weight, and neonatal death were found to be 23.3/1000 live birth, 26.9511000 live birth, 42.49/1000 live birth, 113.75/1000 live birth, and 28.78/1000 live birth respectively. About 28% of newborn babies were malnourished ( <2.5 kg of weight). No significant difference was observed between the two categories of As exposed and non-exposed babies. The majority of the mothers (72%) exposed to As at above 50 ppb gave normal births. A statistically significant difference was observed in the total pregnancy outcome status of the respondent mothers, particularly for low birth weight (p<0.002), premature birth (p<0.006), and abortion (p<0.06) when compared with As exposed and non-exposed groups, after adjustment for maternal education, age of mothers, antenatal care, parity, and household socioeconomic condition. It seems from the study that the rate of adverse pregnancy outcomes including abortion, premature birth, low weight birth, still birth, and post-natal death of the mothers exposed to As above 50 ppb was higher than those of the mothers exposed to As below 50 ppb. However, these differences were not found to be statistically significant for mothers who gave first birth in the year 2002 in spite of drinking As contaminated water. In contrary, a significant difference was observed particularly for spontaneous abortion, premature birth, and low birth weight cases for the mothers who had previous pregnancy history including for the year 2002. Further study is needed to establish this finding by mapping the precise exposure assessment.